(untitled) - Dicken, Peter (New York, 1992)
This book introduce the changing global map, trends in production and trade. The changing global map of international investment, the growth and spread of transnational corporations. Global shift, the picture in different sectors. Stresses and strains of adjustment to global shift.
Keywords: Công nghiệp,Industries; Lịch sử,History; Thế kỷ 21,20th century